Complex Portal 2022: new curation frontiers. Issue Volume 50:Issue D1(2022) (29th October 2021) - Meldal, Birgit H M; Perfetto, Livia; Combe, Colin; Lubiana, Tiago; Ferreira Cavalcante, João Vitor; Bye-A-Jee, Hema; Waagmeester, Andra; del-Toro, Noemi; Shrivastava, Anjali; Barrera, Elisabeth; Wong, Edith; Mlecnik, Bernhard; et al.
Abstract: The Complex Portal (www.ebi.ac.uk/complexportal ) is a manually curated, encyclopaedic database of macromolecular complexes with known function from a range of model organisms. It summarizes complex composition, topology and function along with links to a large range of domain-specific resources (i.e. wwPDB, EMDB and Reactome). Since the last update in 2019, we have produced a first draft complexome for Escherichia coli, maintained and updated that of Saccharomyces cerevisiae, added over 40 coronavirus complexes and increased the human complexome to over 1100 complexes that include approximately 200 complexes that act as targets for viral proteins or are part of the immune system. The display of protein features in ComplexViewer has been improved and the participant table is now colour-coordinated with the nodes in ComplexViewer. Community collaboration has expanded, for example by contributing to an analysis of putative transcription cofactors and providing data accessible to semantic web tools through Wikidata which is now populated with manually curated Complex Portal content through a new bot. Our data license is now CC0 to encourage data reuse. Users are encouraged to get in touch, provide us with feedback and send curation requests through the 'Support' link.